2022
DOI: 10.1021/acsbiomaterials.2c00434
|View full text |Cite
|
Sign up to set email alerts
|

Heparinized Collagen Scaffolds Based on Schiff Base Bonds for Wound Dressings Accelerate Wound Healing without Scar

Abstract: Skin wound healing is a complex process with multiple growth factors and cytokines participating and regulating each other. It is essential to develop novel wound dressings to accelerate the wound healing process. In this study, we developed the heparinized collagen scaffold materials (OL-pA), and the cross-linking reaction was based on the Schiff base reaction between pig acellular dermal matrix (pADM) and dialdehyde low molecular weight heparin (LMWH). Compared with pADM, the OL-pA modified by crosslinking s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…Moreover, the protease-rich environment at the site of regeneration often renders them useless resulting in reduced efficacy and prolonged healing time. , This has led to research in biomaterials that can also mimic the native ECM characteristics in sequestering and stabilizing endogenous GFs, thereby utilizing the therapeutic capability of endogenous GFs in promoting regeneration. Such biomaterials, when employed as dressings, can avoid several consequences of exogenous delivery while reducing the economic burden involved in exogenous delivery . As expected, the heparin-conjugated dressings decorated with micro-pyramids showed around 64% immobilized VEGF, whereas the dressings without heparin showed around 37%, and the flat dressing showed as low as 10% immobilized VEGF.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Moreover, the protease-rich environment at the site of regeneration often renders them useless resulting in reduced efficacy and prolonged healing time. , This has led to research in biomaterials that can also mimic the native ECM characteristics in sequestering and stabilizing endogenous GFs, thereby utilizing the therapeutic capability of endogenous GFs in promoting regeneration. Such biomaterials, when employed as dressings, can avoid several consequences of exogenous delivery while reducing the economic burden involved in exogenous delivery . As expected, the heparin-conjugated dressings decorated with micro-pyramids showed around 64% immobilized VEGF, whereas the dressings without heparin showed around 37%, and the flat dressing showed as low as 10% immobilized VEGF.…”
Section: Resultssupporting
confidence: 67%
“…Such biomaterials, when employed as dressings, can avoid several consequences of exogenous delivery while reducing the economic burden involved in exogenous delivery. 48 As expected, the heparin-conjugated dressings decorated with micro-pyramids showed around 64% immobilized VEGF, whereas the dressings without heparin showed around 37%, and the flat dressing showed as low as 10% immobilized VEGF. The results confirmed that the addition of micro-pyramids indeed enhanced the sequestration ability of the dressings because of the increased surface area.…”
Section: In Vitro Cyto-compatibilitysupporting
confidence: 69%
“…Immediate and effective treatment is crucial to wound healing . Various types of wound dressings have been developed to solve the problem of skin tissue regeneration, including membranes, sponges, scaffolds, and hydrogels. , Therein, hydrogels have attracted much attention because of their exceptional advantages. Hydrogels show high water absorption and could simulate an extracellular matrix (ECM), which provides a suitable microenvironment for wound healing .…”
Section: Introductionmentioning
confidence: 99%
“…However, they cannot keep the wound moist and may adhere to the newly grown granulation tissue, resulting in a secondary injury during dressing changes. Recently, bioinspired hydrogels have demonstrated multiple superiorities over traditional wound dressings and attracted tremendous attention in wound healing applications. Bioinspired hydrogels can not only serve as physical barriers to prevent further injury and infection but also accelerate the wound healing process, by providing a moist environment, draining wound exudate, and facilitating gaseous exchange through their hydrated and porous structures. Except for the biocompatibility, an ideal bioinspired hydrogel-based wound dressing should possess the following characteristics: (i) satisfactory mechanical performances to deal with the stress and strain encountered during the wound healing process; (ii) appropriate adhesion to the wet and dynamic wound surface, which can seal wounds rapidly and function as a long-term physical barrier; and (iii) ability to prevent bacterial infections that significantly delay or hamper wound healing. , In this scenario, multicomponent hydrogels that display the collective beneficial properties of each integrated component have been explored to satisfy the above-described requirements. Different strategies, including the construction of interpenetrating polymeric networks, integration of multilayered hydrogels, and grafting functional components (e.g., molecules or nanoparticles with bioactivities) to the polymeric scaffold, have been developed to create the multicomponent hydrogels as wound dressings. , Generally, the preparation of these hybrid bioinspired hydrogels consists of multiple successive steps and/or time-consuming processes. Alternatively, cross-linking of reactive polymers based on various click reactions provides a fast way to fabricate multicomponent hydrogels for wound healing applications. , Unfortunately, the synthesis of polymers bearing reactive functional groups requires sophisticated protocols and delicate reaction conditions.…”
Section: Introductionmentioning
confidence: 99%